Influences of Temperature on Development and Survival, Reproduction and Growth of a Calanoid Copepod (Pseudodiaptomus dubia). (2009) - Li, Changling; Luo, Xiaoxia; Huang, Xianghu; Gu, Binhe
Abstract : Pseudodiaptomus dubia is a calanoid copepod that is distributed widely in the estuarine-coastal waters of Asia and is a dominant copepod in the shrimp grow-out ponds in southern China. A laboratory culture experiment was conducted to evaluate the influences of water temperature on larval development, survival, and reproduction. Results indicate that within a temperature range from 15 to 35°C, larval development increases as the temperature increases. The water temperature for optimal larval survival rate ranges from 20 to 35°C. Longevity and egg hatching time decrease as the temperature increases from 20 to 35°C. Total fecundity and reproduction frequency increase as the water temperature increases, with the maximum at 30°C. Fecundity and reproduction frequency decrease when the temperature exceeds 30°C. Intrinsic growth rate (rm ) ranges from 0.168 to 0.195 at 25 to 30°C; net reproduction rate (R0 ) and finite growth rate (?) are 163 to 264 and 1.183 to 1.215, respectively, when the temperature is greater than 20 and 35°C; population doubling time (t) varies from 3.556 to 4.128 days at temperatures less than 20 and 35°C. Population generation time (T) is negatively correlated with temperature, with the optimal population growth rate at 25 to 30°C.